Pengembangan Ilmu Berparadigma Integratif - Mohammad Muslih (Proceedings of Annual Conference for Muslim Scholars, 2017)
The construction of integrative scientific paradigm is a grand scientific project, however the success of the reconstruction of a new paradigm that is not enough, because still must be supported by the availability of functional and effective methodology. This paper intends to offer methodology of science development, based on integrative paradigm, which is not only functional and effective, but give guarantee for productivity, as well as safe from the shackles of a practice pseudo-scientific, and excessive practice of ideological science. Scientific development model "methodology of research programs" offered here, on the one hand would be sufficient as an answer to doubts about competability to the Islamic sciences, and on the other hand denied also fear of loss or erosion of Islamic values with increasing scientific research, or development of scientific reasoning in general.